Still in the Woods: Gridlock in the IMF and the World Bank Puts Multilateralism at Risk. Issue 1 (27th October 2014) - Vestergaard, Jakob; Wade, Robert H.
Abstract The Western hegemony of the past 200 years is ending as power shifts towards the East and as Western states lose the authority to uphold a rules‐based multilateral order. In the wake of the Great Crash of 2008 the G20 leaders took steps to bolster the multilateral order, including reform of the governance of the International Monetary Fund (IMF) and the World Bank so as to reflect the increasing economic weight of developing countries. The executive boards of both organizations affirmed that the primary criterion for allocating voting shares should be shares of world GDP. We show that the reforms at the IMF and the World Bank have substantially failed to meet their ostensible objectives. First, in both organizations the developed countries gained voting share relative to GDP share between 2009 and 2014. Second, countries continue to vary widely in their share of votes relative to share of world GDP; in both organizations some countries have six times or more the votes relative to GDP of others. Politicians and analysts should give attention to achieving more equitable governance in these important multilateral organizations. At the end of this article we show how this could be done.